Representation of Bengkulu Provincial DPRD Members in Supporting the Government's “Help the People” Policy - Eceh Trisna Ayuh; Marlinda Irwanti; Siti Nabila Ria (DAWUH : Islamic Communication Journal, 2026)
Regional legislative bodies (DPRD) play a strategic yet underexamined role in ensuring welfare-oriented policies genuinely benefit the public. This study analyzes the representation of Bengkulu Provincial DPRD members in supporting the "Bantu Rakyat" policy, addressing a gap in existing literature that examines DPRD functions generically without linking them to specific pro-people programs at the provincial level. Employing Hanna Pitkin's (1967) Theory of Representation encompassing formalistic, descriptive, symbolic, and substantive dimensions as its analytical framework, this study uses a qualitative library research method supplemented by purposive in-depth interviews with members of Commission I of the Bengkulu Provincial DPRD. Findings reveal that all four representational dimensions are present, though with varying effectiveness. Formalistic representation is evident in active APBD deliberation and policy approval; descriptive representation emerges through members' diverse socioeconomic backgrounds enabling articulation of constituents' needs; symbolic representation appears in public communications that strengthen public trust. Most critically, substantive representation the highest indicator of representational quality is reflected in supervisory activities including field visits, evaluation sessions, and recommendations to improve benefit distribution transparency, though constrained by limited inter-agency coordination and institutional capacity. This study contributes theoretically by applying Pitkin's framework to a provincial legislative context in Indonesia, and practically by providing a diagnostic basis for strengthening the DPRD's substantive role in welfare policy delivery.